A Philip III Tetradrachm Die Pair Recycled by Seleukos I - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2018)
A newly identified Alexandrine tetradrachm type struck from a recycled pair of Philip III dies, recut to include the anchor insignia and name of Seleukos, is to be added to the corpus of Babylonia Uncertain Mint 6A (Opis). It represents a new series in the mint’s output, Series V(a), that is closely allied to, but preceding Series V in the name of Seleukos. It is distinguished from the latter by the presence of the anchor symbol and the archaized depiction of Zeus. It precedes the decision to eliminate the anchor insignia from coinage of Uncertain Mint 6A and thus must be amongst the first, if not the first coin type to bear the name of Seleukos, die linked as it is to the last of the issues in the name Philip III Arrhidaios, the last of the Macedonian pure blood Argead line. Considered in the context of other die links between different series in the corpus of Babylonian Uncertain Mint 6A, this die link has a ritual character, in effect a numismatic statement of the legitimacy of Seleukos as the successor to Philip III Arrhidaios.